2014
DOI: 10.1007/s00894-014-2311-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of the intercalation behaviors of methane hydrate in montmorillonite

Abstract: The formation and mechanism of CH4 hydrate intercalated in montmorillonite are investigated by molecular dynamics (MD) simulation. The formation process of CH4 hydrate in montmorillonite with 1 ~ 8 H2O layers is observed. In the montmorillonite, the "surface H2O" constructs the network by hydrogen bonds with the surface Si-O ring of clay, forming the surface cage. The "interlayer H2O" constructs the network by hydrogen bonds, forming the interlayer cage. CH4 molecules and their surrounding H2O molecules form c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…For the adsorbed water molecules on hydrophilic nano-SiO 2 surface, they would form hydrogen bonds with the hydroxyl group, which is stable against the influence of the hydrophobic methane molecules through the weak van der Waals force [29] . Indeed, molecular dynamic simulation showed that the water at the surface of clay could not be considered bulk-like and these water molecules constructed the network by hydrogen bonds with the surface Si-O ring of hydrophilic clay [45,46] . Therefore, the adsorbed water molecules aligned on the surface of the nanoparticles become difficult to re-arrange themselves to form a clathrate hydrate structure surrounding the CH 4 molecules.…”
Section: The Possible Mechanism Of Hydrate Inhibition Of Hydrophilic mentioning
confidence: 99%
“…For the adsorbed water molecules on hydrophilic nano-SiO 2 surface, they would form hydrogen bonds with the hydroxyl group, which is stable against the influence of the hydrophobic methane molecules through the weak van der Waals force [29] . Indeed, molecular dynamic simulation showed that the water at the surface of clay could not be considered bulk-like and these water molecules constructed the network by hydrogen bonds with the surface Si-O ring of hydrophilic clay [45,46] . Therefore, the adsorbed water molecules aligned on the surface of the nanoparticles become difficult to re-arrange themselves to form a clathrate hydrate structure surrounding the CH 4 molecules.…”
Section: The Possible Mechanism Of Hydrate Inhibition Of Hydrophilic mentioning
confidence: 99%
“…Electrolytes can reduce the chemical potential of hydrate-forming molecules (H 2 O and N 2 O) and enter open cavities of hydrate structures (Svartaas et al, 2000;Lamorena and Lee, 2008;Kyung et al, 2015). Additionally, their steric effects (construction/destruction) of the hydrogen-bond network among water molecules can distort the hydrate structure (Yan et al, 2014). Ultimately, for complex reasons, the driving force of hydrate nucleation and growth were depressed, and the formation kinetics for N 2 O hydrate slowed down in the presence of electrolytes.…”
Section: Effect Of Electrolytes On N 2 O Hydrate Formation Kineticsmentioning
confidence: 98%
“…It is known that the effects of soil minerals on hydrate formation kinetics are complex because many factors (e.g., surface area, pore size, intercalation of water molecules, and dissolved chemical species) can affect hydrate formation on the surfaces, and in the pores, of soil minerals (Lamorena and Lee, 2008;Yan et al, 2014). Table 3 shows the surface area, pore size, concentrations of dissolved cations, and solvation energy of each soil mineral.…”
Section: Effect Of Soil Minerals On N 2 O Hydrate Formation Kineticsmentioning
confidence: 99%
“…The montmorillonite layer structure can expand and contract its structures without crystallographic change. These expansions depend on the IS content (water/polar molecule) and the surrounding environment (relative humidity rate) [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%